Usage of irrigation elements by means of water-efficient technology in irrigating intensive apple gardens through soil and dynamics of seeping moisture - Juraev Fazliddin U.; Salman Maher; Karimov Golib H.; Ergashov Zuxriddin Ju.; Urinov Eldor F. (E3S Web of Conferences, 2024)
The article presents the results of theoretical and experimental research on the cultivation of intensive orchards with the method of watering through the soil. These methods and elements are for the first time applied to intensive gardens. During the research, we studied both the movement and height of the wetting contour over time H, the radius of the width L, and the curve area of the irrigation norm W m3/ha were relatively chosen.